Evidence to the Need for a Unifying Framework: Critical Consciousness and Moral Education in Adolescents Facilitate Altruistic Behaviour in the Community - Gabriela Monica Assante; Nicoleta Laura Popa; Tudorița Grădinariu (Behavioral Sciences, 2022)
Background: Critical consciousness represents an emancipatory pedagogical process whose central goal is developing the necessary skills to identify and act in the direction of changing social limitations. An important kind of action that helps challenge social limitations is altruistic behaviour. Moreover, moral values could enhance the effect of critical consciousness on altruistic behaviour. Method: This study aims to provide some empirical support for the benefits of a unifying framework between moral education and critical consciousness by exploring the association between critical motivation and moral foundations, and the moderating role of groups’ status (disadvantaged versus privileged) within this association. The present research explores the link between critical consciousness, altruistic behaviour, and the mediational role of moral foundations. The data was collected from participants studying in urban areas and disadvantaged rural areas. Hence, the socio-economic status of the individuals (disadvantaged groups versus privileged groups) is considered a moderator in this dynamic. The study sample comprised 1031 adolescents aged 13–19 (M = 16.51, SD = 1.54). Results: The findings emphasise that fairness and care moral foundations mediate the relationship between critical motivation and altruistic behaviour, and the moderator role of group status. In conclusion, the poor development of critical motivation in disadvantaged groups influences moral values development and, ultimately, affects individual behaviour in the community.